Coffea arabica yields decline in Tanzania due to climate change: global implications - Craparo, Alessandro Carmelo William; Asten, Piet J.A. van; Läderach, Peter R.D.; Jassogne, Laurence T.P.; Grab, S.W. (Elsevier, 2015)
Coffee is the world’s most valuable tropical export crop. Recent studies predict severe climate change impacts on Coffea arabica (C. arabica) production. However, quantitative production figures are necessary to provide coffee stakeholders and policy makers with evidence to justify immediate action. Using data from the northern Tanzanian highlands, we demonstrate for the first time that increasing night time (Tmin) temperature is the most significant climatic variable responsible for diminishing C. arabica yields between 1961 and 2012. Projecting this forward, every 1 °C rise in Tmin will result in annual yield losses of 137 ± 16.87 kg ha−1 (P = 1.80e-10). According to our ARIMA model, average coffee production will drop to 145 ± 41 kg ha−1 (P = 8.45e-09) by 2060. Consequently, without adequate adaptation strategies and/or substantial external inputs, coffee production will be severely reduced in the Tanzanian highlands in the near future. Attention should also be drawn to the arabica growing regions of Brazil, Colombia, Costa Rica, Ethiopia and Kenya, as substantiated time series evidence shows these areas have followed strikingly similar minimum temperature trends. This is the first study on coffee, globally, providing essential time series evidence that climate change has already had a negative impact on C. arabica yields.